Harnessing ICT strategies for ACP agriculture - Lohento, Ken; Liyanage, Harsha (Technical Centre for Agricultural and Rural Cooperation, 2013)
The 2003 and 2005 World Summits on the Information society called for the development of ICT strategies for all sectors. But more is needed for effective e-agriculture strategies in ACP countries.